Pengaruh Kesejateraan Pegawai, Kepuasan Kerja, dan Komitmen Organisasi terhadap Kinerja Pegawai pada Dinas Lingkungan Hidup Kota Malang - Dwiningsih, Sri; Rohman, Fatkur (STIE Kertanegara Malang, 2023)
ABSTRACT This study aims to determine the effect of Employee Welfare, Job Satisfaction, and Organizational Commitment on Employee Performance at the Malang City Environmental Service. The method used by the author in conducting this research is descriptive analysis method and multiple linear regression analysis. Data processing was carried out using IBM SPSS STATISIC 21. The population of this study were daily employees of the Malang City Environmental Service with the number of samples taken according to the researcher's criteria of 67 employees. The results of the partial study of the Employee Welfare variable have a significant effect on Employee Performance, the Job Satisfaction variable has no significant effect on Employee Performance, and the Organizational Commitment variable has no significant effect on Employee Performance at DLH Malang City, simultaneously the variable Employee Welfare, Job Satisfaction, and Organizational Commitment has a significant effect on employee performance at DLH Malang City. Keywords: Employee Performance, Employee Welfare, Job Satisfaction, and Organizational Commitment